Estudo da estabilidade do biodiesel de crambe e soja - Wazilewski, Willian Tenfen (2012)
Biodiesel quality is critical to the successful commercialization of this fuel, so the product must meet some worldwide established parameters to guarantee their full environment roll functionality. Within these parameters there is the kinematic viscosity which may be affected due the degradation of the biofuel, such degradation occurs due atmospheric disturbances which all forms of organic matter are exposed to, and this degradation is accentuated when exposed to high temperatures or in contact with a catalyst matter. As a result of this, a factor that relates the degrees of resistance of a product to different oxidizing agents were created called as oxidation stability. This work aimed to study the oxidative stability of biodiesel produced from vegetable oil of soy and crambe. For this study the techniques of infrared spectroscopy, refractive index at 40 ° C and kinematic viscosity at 40 ° C were used to monitor the level of oxidation of the biodiesel. Viscometric studies revealed that biodiesel of crambe is more stable than soybean when they were exposed to thermal stress in an incubator at 130 ° C, with the addition of 5 and 10% of crambe biodiesel it reduces the viscosimetric change about 43,9% compared to pure soybean biodiesel. Looking at the index of refraction were found that the variation, in the case of pure soybean biodiesel, was about 0.0042 and its blends were 0.0028, 0.0025 and 0.0022 for 5, 10 and 20% of crambe biodiesel, respectively, compared to pure soybean biodiesel would be a stabilization of 33.3, 41.4 and 47.6% for the blends with 5, 10 and 20% of crambe biodiesel, respectively. By infrared spectroscopy it is clear that there was a formation of carbonyl grouping more intense in the soybean biodiesel compared to crambe biodiesel subjected to thermal stress for the same period.